2017
DOI: 10.1007/s11432-017-9189-6
|View full text |Cite
|
Sign up to set email alerts
|

Survey of recent progress in semantic image segmentation with CNNs

Abstract: In recent years, convolutional neural networks (CNNs) are leading the way in many computer vision tasks, such as image classification, object detection, and face recognition. In order to produce more refined semantic image segmentation, we survey the powerful CNNs and novel elaborate layers, structures and strategies, especially including those that have achieved the state-of-the-art results on the Pascal VOC 2012 semantic segmentation challenge. Moreover, we discuss their different working stages and various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 63 publications
0
26
0
1
Order By: Relevance
“…CNNs are by far the most successfully implemented NN algorithms, which has many real-world applications, particularly in image classification such as object detection, [54] facial recognition, [55] and image segmentation. [56] In the past decade, CNN has seen several major breakthroughs in image processing applications and produced several specialized high-performance frameworks such as AlexNet, [33] YOLO9000, U-net, [57] GoogLeNet, [58] VGG, [59] among others. A standard CNN model comprised three building blocks, which are the data input, feature learning, and training and classification ( Figure 7).…”
Section: Convolution Neural Networkmentioning
confidence: 99%
“…CNNs are by far the most successfully implemented NN algorithms, which has many real-world applications, particularly in image classification such as object detection, [54] facial recognition, [55] and image segmentation. [56] In the past decade, CNN has seen several major breakthroughs in image processing applications and produced several specialized high-performance frameworks such as AlexNet, [33] YOLO9000, U-net, [57] GoogLeNet, [58] VGG, [59] among others. A standard CNN model comprised three building blocks, which are the data input, feature learning, and training and classification ( Figure 7).…”
Section: Convolution Neural Networkmentioning
confidence: 99%
“…Earlier studies [219] have shown the potential of deep learning based approaches. There have been more recent studies [68] which cover a number of methods and compare them on the basis of their reported performance. The work of Garcia et al [66] lists a variety of deep learning based segmentation techniques.…”
Section: Motivationmentioning
confidence: 99%
“…DNNs, such as Convolutional Neural Networks (CNNs), powerful for computer vision tasks [13], Recurrent Neural Networks (RNNs), for natural language processing, are all generally layer-centric, hierarchically organized models containing multiple types of layers. These layers can be categorized [20] as below:…”
Section: Layer-centric Training Processmentioning
confidence: 99%